Recording and interpretation of vital signs in a selected private hospital in the KwaZulu-Natal province of South Africa. (2020) - Graan, Anna C. van; Scrooby, Belinda; Bruin, Yolanda
Abstract: Background: Enrolled Nurses (ENs) and Enrolled Nursing Auxiliaries (ENAs) are responsible for the monitoring of vital signs as an essential indicator of patients' physiological deterioration. Monitoring are essential for early recognition of and responding to signs of deterioration as delayed responses could severely affect patient safety. Objectives: This research study, (1) describe the accuracy of recording and the ability of ENs and ENAs (2) interpret the data presented during the assessment of vital signs at a selected private hospital in KwaZulu-Natal. Design and sample: A quantitative, descriptive design was used. Methods: The population (N = 89) consisted of permanent ENs (n = 27) and ENAs (n = 47). Part-time nurses working for an agency were also invited. A sample total of 64 respondents, comprising 20 ENs and 44 ENAs, participated in the study. Ethical permission: Ethical clearance and permission from the organization head office was obtained. Results: The data, reveals a young workforce, with 55% of respondents being between 26 and 35 years of age. Results from the questionnaire indicate that the nurses with more nursing experience and permanently employed achieved a higher score in the knowledge component. Analysis of the documentation, showed that the implementation record was not always correctly identified and that 29.6% of the ENs and ENAs did not enter the vital signs data correctly on the implementation record or rapport abnormalities to the professional nurse in charge. Conclusion: The gaps identified during the assessment of vital signs while working at a private hospital put patients at risk and severely affect quality care.